"Dual awakening" - Zalta, Anja (Poligrafi, 2022)
The paper presents the concept of “dual awakening”, which is based on the Buddhist mindfulness appropriated by socially engaged Buddhism as a method to recognize and implement a “wholesome” paradigm on both the social and in-dividual level. In the first half of the paper, I analyze the idea of “dual awakening” in the Southeast Asian context, especially in the case of the Sarvodaya Sramadana movement in Sri Lanka, In the second part of the paper, I review some of the re-search on (mindfulness) meditation in the West to critically evaluate the de-con-textualization of transferring Buddhist ideas and methods (such as cultivating empathy and compassion as a basis for social action) into the Western modernist paradigm.
Keywords: Buddhism; budizem; Chinese religion; družbeno angažirani budizem; družbeno delovanje; kitajska religija; meditacija; meditation; mindfulness; Sarvodaya; social action; socially engaged Buddhism